SOME ASPECTS OF THE “SATELLITE CITIES” PROJECT IN THE FERGHANA REGION (Scientific journal of the Fergana State University, 2024)
The article covers in detail the problems of rapid population growth and the development of the socio-economic situation of the country, expansion of the network and density of cities in society. These processes clarified that the risks that could arise from increasing the city's dependency ratio should be addressed by reducing its dependency ratio. Therefore, the article analyzes the socio-economic significance of the organization of satellite cities using the example of cities in the Fergana region.